Antioxidant property of secondary metabolites from Garcinia genus: A short review - Kazmierczak, Elton; Magalhães, Cássia Gonçalves; Picada Pereira, Romaiana (Eclética Química, 2023)
Species from the Garcinia genus (Clusiaceae family) are used in the treatment of many diseases and metabolic disorders frequently associated with the oxidative stress. The characteristic metabolites found in this genus are xanthones and benzophenones, which have antioxidant properties, among relevant biological potentials. This review provides a specific vision about antioxidant activity of Garcinia species, reporting in vitro and in vivo assays, described from the last five years. The research about antioxidant properties of Garcinia species and their constituents can be directed in the development of new medicines and drugs.